Fusarium poae Pathogenicity and Mycotoxin Accumulation on Selected Wheat and Barley Genotypes at a Single Location in Argentina - Stenglein, Sebastián (2014)
Fusarium poaeis a relatively weak pathogen with increasing importance in cereal grains, principally due to its capacity to produce several mycotoxins. In this study, we evaluated the pathogenicity and toxin accumulation of individualF. poaeisolates on wheat and barley under natural conditions for 3 years. Analysis of variance demonstrated significant differences for year–genotype, year–isolate, genotype–isolate, and year–genotype–isolate interactions for both incidence and disease severity. Based on contrast analysis, ‘Apogee’ was more susceptible than the other wheat genotypes, wheat genotypes were more susceptible than barley genotypes, durum wheat genotypes were more susceptible than bread wheat genotypes, and barley genotype ‘Scarlett’ had greater symptom development per spike than the other barley genotypes. Neither HT-2 nor T-2 toxins were detected in the grain samples. However, high levels of nivalenol were found in both wheat and barley samples. The increased reported isolation ofF. poaefrom wheat and barley and the high capacity of this fungus to produce nivalenol underlie the need for more studies onF. poae–host interactions, especially for barley.